Sensitizing the social-ecosystems of outdoor sport environments: A comprehensive framework - Trendafilova, Sylvia; Ziakas, Vassilios (Frontiers in Sports and Active Living, 2022)
This paper focuses on the social features character of participation in outdoor sports that plays a significant role in the lived experience of participants, and in their interactions with the environment. These embodied interactions can bridge nature and culture, and inform interventions for more sustainable ecosystems. Conceptual methods were used to explain the sport-nature-culture nexus and postulate an interdisciplinary framework of social sport ecology, incorporating management, nature sports, neo-tribalism, and non-representation theoretical perspectives. The proposed framework suggests that multi-sensory stimuli, embodied sport practices and neo-tribal cultural values shape the ‘sports ecosphere’, which needs to be attuned with the affective/cognitive dimensions of experience in ways that build caring cultures for the environment. The significance of this work lies in its comprehensive perspective approach to the environmental management of outdoor sports by demonstrating the critical role of politics, culture, experience and movement in contemporary sport. It suggests a holistic approach of social sport ecology to better understand and reimagine the environmental practices and character of outdoor sports.